Regime jurídico das medidas coercitivas atípicas na execução de obrigações pecuniárias, à luz do Art. 139, IV, do CPC - Steinberg, José Fernando (2020)
In general terms, the aim of this doctoral thesis is to study and understand the main innovations brought by the new Code of Civil Procedure, and its reflexes in relation to the powers and duties of the judge, according to the provision of article 139, item IV. Lastly, specifically, regarding the atypical nature of executive means in pecuniary obligations, it seems quite healthy that criteria should be established for the adoption of coercive, inductive and mandatory measures to the detriment of the perpetrator, who must always have his or her human dignity preserved. As is well known, such powers contain a general clause and in view of the atypicality of such measures, the judge must evaluate, according to the specific case, the most appropriate technique to apply, using the principle of proportionality, so that, among inductive, coercive, mandatory or sub rogatory measures, decide on the basis of the legal system and without the risk of arbitrariness. Thus, it is urgent to understand very well the scope of this new power-duty of the judge, brought by art. 139, IV, CPC, always critically and independently, taking advantage of its innovations, however, rejecting what does not meet the fundamental postulates of due process of law, which should always guide the hermeneutic procedural activity. At the end of this paper, and after analyzing the main aspects of the subject in study, we made our proposal of criteria for the proper application of the atypicality of the executive means in pecuniary obligations, in accordance with the postulates outlined by the Federal Constitution of 1988, which should serve as lens and filter of doctrinal and jurisprudential activity. We hope that in some way we contributed, especially, by providing criteria for the practical application of this general power of coercion by Brazilian judges